First-principles theory of electronic structure and magnetism of Cr nano-islands on Pd(1 1 1). (14th November 2016) - de Melo Rodrigues, Debora Carvalho; Pereiro, Manuel; Bergman, Anders; Eriksson, Olle; Klautau, Angela Burlamaqui
Abstract: We report on the electronic structure, magnetic moments and exchange interactions of one- and two-dimensional Cr clusters on a Pd(1 1 1) substrate, using a real-space method based on density functional theory in the local spin density approximation. We find in general that for the investigated clusters, the magnetic moments are sizeable and almost entirely of spin-character. We demonstrate that the interactions in general are dominated by nearest-neighbor antiferromagnetic Heisenberg form, which implies that Cr on Pd(1 1 1) forms an ideal model system, in which clusters of almost any shape and size can be investigated from a Heisenberg Hamiltonian, using a nearest-neighbor exchange model. We have also found that complex magnetic structures can be realized for linear chains of Cr, due to a competition between exchange interaction and a weaker Dzyaloshinskii–Moriya interaction.